Tiktok, Instagram and Presidential Election: A Study to Understand How Politainment in Indonesian Political Campaigns 2024 - Kulau, Febriansyah (Informasi, 2024)
The development of technology has brought about various transformations in the lines of people's lives, one of which is in political contestation. A political contestation in Indonesia has just passed namely the 2024 General Election. The Indonesian people elected 4 Legislative Members and 1 Pair of Presidential and Vice Presidential Candidates in that election. There were three candidate pairs in the 2024 presidential election. Candidate Pair Prabowo-Gibran, Candidate Pair Anies-Muhaimin and Candidate Pair Ganjar-Mahfud. In the campaign process, something was interesting, namely that the discourse battle had shifted to a non-discourse battle. One is politainment, which the candidate pairs presents to the public on social media. Politainment itself refers to the equivalent of the words politics and entertainment. This is interesting because political contestation is very close to the battle of ideas and discourse in the campaign process. However, in the 2024 presidential election, this has shifted. Therefore, this is interesting to examine further. This study uses a qualitative approach to dig deeper into politainment in the 2024 Presidential Election political campaign. The data will be selected using purposive sampling techniques, and then the data that has been obtained will be analyzed using qualitative thematic analysis techniques. This study found that politainment is used by presidential and vice presidential candidate pairs to wrap messages in political campaigns